Time Trend Analysis of Cancer‏ Incidence in Caspian Sea, 2004 - 2009: A Population-based Cancer Registries Study (northern Iran) - Hamid Salehiniya; Sakineh Ghobadi-Dashdebi; Hosein Rafiemanesh; Abdollah Mohammadian-Hafshejani; Mostafa Enayatrad (Babol University of Medical Sciences, 2016)
Background: Cancer is a major public health problem in the world. In Iran especially after a transition to a dynamic and urban community, the pattern of cancer has changed significantly. An important change occurred regarding the incidence of cancer at the southern shores of the Caspian Sea, including Gilan, Mazandaran and Golestan province. This study was designed it investigate the epidemiology and changes in trend of cancer incidence in the geographic region of the Caspian Sea (North of Iran). Methods: Data were collected from Cancer Registry Center report of Iran health deputy. Trends of incidence were analyzed by joinpoint regression analysis. Results: During the study period year (2004-2009), 33,807 cases of cancer had been recorded in three provinces of Gilan, Mazandran and Golstan. Joinpoint analysis indicated a significant increase in age-standardized incidence rates (ASR) with an average annual percentage change (AAPC) 10.3, 8.5 and 5.2 in Gilan, Mazandaran and Golestan, respectively. The most common cancer in these provinces were correspondingly cancer of stomach, breast, skin, colorectal and bladder, respectively. Conclusion: The incidence of cancer tends to be increasing in North of Iran. These findings warrant the epidemiologic studies are helpful in planning preventive programs and recognition of risk factors.